Managing Responsible Agricultural Investments Using an Open Source Solution - Mulugeta Tadesse Geleta (African Journal on Land Policy and Geospatial Sciences, 2018)
To address food insecurity, the Government of Ethiopia embarked on a rapid transformation in the agriculture sector to increase production, productivity, market access and create employment opportunities by promoting large scale agricultural investment projects. However, progress towards achieving set objectives has been rather limited so far due to various challenges. One of the major challenges is that information on commercial farming is outdated and unreliable for decision making. This paper describes the development of an Agricultural Investment Information Management System for Commercial and Contract Farming (AIIMS-CCF), which provide solution to challenges related to information management. AIIMS-CCF is distributed system based on Free and Open Source Software. AIIMS-CCF will have rich features that facilitate the management of accurate, consistent and reliable data and information required for land governance and decision making and will provide tools for monitoring the performance of agricultural investments in terms of their contributions to the national economy.